Comparative Analysis of Financial Performance Before and After Mergers and Acquisitions - Fellicia Novita; Rosyeni Rasyid (Financial Management Studies, 2022)
This study aims to analyze the company's financial performance through financial ratios before and after mergers and acquisitions of companies listed on the Indonesia Stock Exchange with the period studied 2016-2019. Manufacturing companies listed on the Indonesia Stock Exchange are the population in this study. While the sample in this study used purposive sampling method in order to obtain 13 samples. The type of data used in this study is secondary data obtained from the website www.idx.co.id. The analytical method used is the Paired Sample T-test Difference. The results of this study indicate that there are differences before and after mergers and acquisitions in certain financial ratios, namely the Return on Assets and Price Earning Ratios, but the other ratios tested did not show any differences when studied.